Enhancement of Spurious Signal Suppression in Microstrip Mixers by Load Resistor Termination - Catur Apriono; Abdurrasyid Ruhiyat; Farohaji Kurniawan; Arokiaswami Alphones; Fitri Yuli Zulkifli (Sensors)
The mixer is an essential component in RF transceiver subsystems. It has a role in shifting the signal frequency for more convenient processing of up-conversion as well as down-conversion. Despite generating the desired signal, the mixer also generates spurious noise that wastes power and reduces the performance of the overall system. This research proposes the design of a microstrip mixer that can enhance the suppression of spurious signals by utilizing the characteristics of the load resistor termination. The simulation results show that by adding the load resistor, the parasitic electrical field on the diode and the reflection signal inside the mixer can be reduced. The measurement result also validates that the suppression of the spurious signal is enhanced, where the signal-to-noise ratio can reach above 50 dB on the single-balanced mixer and above 60 dB on the double-balanced mixer.